Local Government and Its Relationship with The Central Government In Light of Iraqi Legislations - Abdulateef, Arwaa Fakhri (International Journal of Membrane Science and Technology, 2023)
Objective: The study deals with the situation in Iraq after 2003, which is a new stage in the political and administrative history of Iraq after the adoption of the federal system and the transition from the centralization system to the administrative decentralization system, which was explicitly stated in the Iraqi constitution of 2005, and the law of irregular governorates in Region No. 22 for the year 2008. Method: the descriptive approach was used in explaining the concept of local governance and local administration and the differences between the two concepts, using the comparative method in defining the competencies of each of the central government and its local units in accordance with the Iraqi constitution of 2005 and comparing that with the law of irregular governorates in the region No. 22 of the year 2008 and its amendments. Results: Because the federal experience in Iraq came as a result of the occupation and its repercussions and not as a result of the maturation of social and political awareness, its legislation was characterized by weakness with regard to the distribution of competencies for both the local administration and the central administration. Also, the Governorates Law No. 22 of 2008 failed to set a general policy for local governments for their establishment, organization, management and the way of distributing their competencies, which led to a conflict between the competencies of each of the local governments and the central government.